Resection of an immature intrapericardial teratoma from a premature neonate presenting as hydrops foetalis - Mazalan, S. Laura; Yubbu, Putri; Velayudham, V. Ramesh (Cambridge University Press, 2022)
Intrapericardial teratoma is a germ-cell tumor that typically arises from the base of the heart. This rare cardiac tumour is the second most common tumor diagnosed in fetuses and newborn. Although benign, it can be massive in size causing direct compression on the heart and associated with significant pericardial effusion resulting life-threatening complications such as cardiac tamponade, heart failure, foetal hydrops, and sudden death. Early antenatal diagnosis and surgical intervention improve the survival. We present a case of immature intrapericardial teratoma diagnosed at 25 weeks of gestation but required multiple foetal pericardiocentesis and premature delivery due to massive pericardial effusion. The importance of multidisciplinary team approach to ensure successful management was highlighted in this case report.